Factors Related to Resilience Among Elderly Cancer Patients Receiving Chemotherapy - Limwattanathawornkul, Ingon; Jullamate, Pornchai; Piphatvanitcha, Naiyana (Journal of Nursing, Siam University, 2019)
ABSTRACT The purposes of this research were to study the resilience of the elderly cancer patients receiving chemotherapy and its related factors including hope, coping, sense of coherence and social support. Ninety seven elderly cancer patients receiving chemotherapy at general male and female wards of Chonburi Cancer Hospital, Chonburi province. Instruments used in this study consisted of The Demographic Data Questionnaire, Hope Questionnaire, Coping Questionnaire, The Sense of Coherence Questionnaires, Social Support Questionnaire, and Resilience Scale Questionnaire. Data were collected during February to May 2017 and analyzed by use descriptive statistics and Spearman’s rank correlation coefficients were computed for data analysis. The results indicated that the majority of elderly cancer patients receiving chemotherapy had Hope, coping, sense of coherence and social support had moderately and positively significant correlation with resilience of elderly cancer patients receiving chemotherapy. (r = .56, p < .01; r = .58, p < .01; r = .54, p < .01; r = .40, p < .01 respectively) Findings suggested that nurses should develop programs or interventions for promoting resilience among elderly cancer patients receiving chemotherapy by applying hope, coping, sense of coherence and social support into those interventions to promote resilience of elderly cancer patients receiving chemotherapy.